Determinants of Employee Performance: The Role of Leadership Style, Competence, Integrity and Work Motivation - Nika Saputra; Syamsir Syamsir (Jurnal Ilmiah Ilmu Administrasi Publik, 2022)
This study analyzes the effect of leadership style, competence, integrity, and work motivation on the performance of sub-district employees in Padang City. The population in this study were all employees in each sub-district in Padang City, with as many as 761 employees. The sampling technique used was the purposive sampling technique, with the number of samples as many as 266 respondents. The data analysis technique is descriptive qualitative analysis with a quantitative approach and partial least square structural equation modelling (PLS-SEM) analysis. Calculations made with AMOS version 22 show that the results show that leadership style has a significant effect on employee performance, that competence has a significant effect on employee performance, that integrity has a significant effect on employee performance, that work motivation has a significant effect on employee performance, that leadership style has a significant effect on employee work motivation, that competence has a significant effect on employee work motivation, that integrity has a significant effect on employee work motivation, that integrity has a significant effect on employee work motivation, that leadership style has.